Value Theory in Islamic Economics: Implications for Market Structures and Pricing Mechanisms - Albar, Kholid; Misbach, Irwan; Muin, Rahmawati (JURNAL ISLAM NUSANTARA, 2024)
This article discusses the analysis of value theory in the context of markets and prices in Islamic economics. Using a qualitative approach, this study examines how the moral and ethical values contained in Islamic teachings affect market dynamics and pricing. Referring to Surah Al-Baqarah (2:188) which emphasizes the importance of fairness in transactions, as well as Surah Al-Anfal (8:28) which reminds of the need for transparency, this study shows that pricing in the Islamic economy should not only be based on economic factors, but also on the underlying sharia principles. Recent data shows that the halal product market is experiencing significant growth, with the market value estimated to reach USD 2.3 trillion by 2023. Growing consumer awareness of Shariah-compliant products, as reflected in Surah Al-Maidah (5:88), is creating greater demand for ethical goods and services. The research also identified challenges faced in the application of value theory, including fraudulent practices and unfairness in pricing. Therefore, the need for regulations that support the development of halal markets and Islamic economic education is crucial. The conclusion of this study shows that the application of value theory in the context of markets and prices is expected to create a more just and sustainable economic environment, as well as contribute to the development of economic practices based on sharia principles.